Peran Pengalaman Berwirausaha Dalam Memilih Sumber Pembiayaan Family Funding Bagi Petani Garam Di Madura - Wulan Safitri; Moh. Zaki Kurniawan; M. Boy Singgih Gitayuda (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
One form of financing source that has an informal nature originating from capital sources from family or relatives is often referred to as family funding. Family funding is chosen by business actors as an alternative due to several factors. The method used is descriptive with a quantitative approach by applying multiple linear regression models. The research is located on the island of Madura. The object of this research is salt farmers in Pamekasan Regency. The sampling technique used in this research is using a purposive sampling approach with a sample of 40 salt farmers. The independent variable chosen in the study is entrepreneurial experience, while the dependent variable in the research is family funding. The results of the study concluded that the entrepreneurial experience variable had no effect on choosing the source of family funding for salt farmers in Madura.